Implementasi Kombinasi Secret Sharing dan Steganografi Citra Least Significant Bit dengan QR Code - Marwati, Rini; Pebriani, Dwi Putri; Rachmatin, Dewi (Indonesian Journal of Applied Mathematics, 2025)
Information security becomes very important as long as information technology continues to develop. This research combines Shamir Secret Sharing (Scheme ( , )) cryptography and Least Significant Bit (LSB) steganography to improve information security in the aspect of confidentiality. The need to collect a minimum number of shares, Scheme ( , ) method makes it more difficult for hackers to reconstruct the message. The implementation of the combination of cryptography and steganography produces an application program created with Python programming languange version 3.11.2, where the Scheme (t,w) used is and RGB image as the cover object of LSB method. In determining the location of image pixels that will be inserted into the message, random numbers generated by the Linear Congruential Generator (LCG) algorithm is used. The program can create a share of text messages with a maximum of 8 characters contained in ASCII characters 32 to 126. The result obtained from the share construction program is QR codes that refers to the stego image that has been inserted by the share, so that the existence of information in the QR code is difficult to know. The program can also reconstruct the message back from QR codes.